MORPHOLOGICAL CHARACTERISTIC OF SPERMATOGONIA AND TESTES DISSOCIATION : A Preliminary Study for the Germ Cell Transplantation in Giant Gouramy (Osphronemus gouramy) - Irma Andriani; Ita Djuwita; Komar Sumantadinata; Muhammad Zairin Junior; Harton Arfah; Alimuddin Alimuddin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
The recent study were attempting to develop spermatogonial germ cell transplantation as a tool to preserve and propagate male germ-plasm from endangered fish species, as well as to produce surrogate broodstock of commercially valuable fish. Spermatogonia identification and testes dissociation were the first necessary steps to obtain highly amount and viable population of spermatogonia as donor cells for transplantation. Using giant gouramy testes as a model, spermatogonia was histological characterized and two methods of testes dissociations were compared (i.e. medium A contained 0.5% trypsin in PBS and medium B contained 0.5% trypsin and DNase 10 IU/μL in PBS complemented with CaCl2, Hepes and FCS). Optimal incubation times (1, 2, 3, 4 and 5 hours) in dissociation medium were also determined. Freshly isolated testes of immature giant gouramy were minced in dissociation medium and then incubated to get monodisperce cell suspension. Parameters observed were number and viability of spermatogonia (ø > 10 μm). The viability was analyzed using trypan blue exclusion dye. The results showed that the average number of spermatogonia observed in medium B was higher than in medium A (P<0.05), meanwhile the viability of spermatogonia between medium A and B were not significantly different (P>0.05). The viability of spermatogonia decreased by the increasing duration time of dissociation. The viability of spermatogonia started to decrease significantly in 2 hours incubation time in medium A and 4 hours incubation time in medium B (P<0.05). In conclusion, application of dissociation medium B yielded higher number of viable spermatogonia than dissociation medium A.